Konjac glucomannan: A key ingredient for controlling fibrous structure formation in walnut protein and wheat gluten meat analogues during the high-moisture extrusion process - Lei, Shuwen; Zhao, Chunyan; Miao, Yue; Zhao, Hong; Fu, Xiaoping; Peng, Chunxiu; Gong, Jiashun (Food science & technology, 2025)
This study focused on exploring the impact of different konjac glucomannan (KGM) contents (0, 1, 3, 5 g/100 g) on fibrous structure formation in walnut protein and wheat gluten high-moisture meat analogues (HMMAs). The results showed that KGM enhanced hardness, chewiness, springiness and fibrous degree of high-moisture meat analogues. KGM was observed to modify fibrous structure formation and orientation in HMMAs. Comprehensive analysis of the effect of KGM on the quality and microstructure of HMMAs revealed that when the addition content of KGM was 3 g/100 g, HMMAs had the highest fibrous degree, and the fibrous structure displayed strong toughness, and formed a more consistent, continuous and dense structure. Consequently, HMMAs with 3 g/100 g KGM was chosen for study the mechanism of KGM controlling fibrous structure formation in HMMAs during the high-moisture extrusion process. 3 g/100 g KGM improved HMMAs’ thermal stability and apparent viscosity. 3 g/100 g KGM promoted more covalent and non-covalent bonds formation, thereby improving the cross-linking degree of protein molecules. 3 g/100 g KGM promoted natural protein disintegration from high-to low-molecular-weight forms, mainly with protein subunits 30–40 kDa. In addition, 3 g/100 g KGM enhanced protein structure orderliness. This study offers valuable information for developing plant-based protein meat analogues that have rich fibrous structures through the addition of exogenous polysaccharides. [Display omitted] •KGM has a positive effect on the quality characteristics of HMMAs in WP and WG.•KGM could regulate the more oriented fibrous structure of WP and WG-blended HMMAs.•KGM increases the ordered structure content of WP and WG meat analogues.•KGM promotes disintegration of proteins from high-to low-molecular-weight forms.